Studi Experimental Pembuatan Karbon Aktif Dengan Variasi Laju Alir Massa Air Terhadap Massa Penyimpanan Biogas - Mardika, I Nengah; Wijaksana, Hendra; Sucipta, Made (Teknik Desain Mekanika, 2022)
Abstract The Integrated Agricultural System is a program of the Bali Provincial Government that integrates livestock and agricultural activities for community development in the village. Simantri activities aim to increase the number of livestock populations, agricultural area, and the quality of the products produced. Biogas produced from cow dung waste from Simantri can be used for household and community purposes. The use of biogas for the wider community has not been optimal due to the limitations of biogas processing. In this study, it is expected to find out the potential for using bamboo as an adsorbent as a biogas storage medium with the ANG (Adsorption Natural Gas) system. The method used is the adsorption of biogas at a storage pressure of 100 psi with a weight of 70gram bamboo activated carbon as the adsorbent, activated carbon with a mesh size of 35-45 at carbonization and with steam activation temperature of with variations in the water mass flow rate of 0.025 kg?s, 0.075 kg?s and 0, 1 kg?s. The results of the research in biogas storage showed that the highest mass absorption occurred at 0.1 kg?s water mass flow rate variation which was able to store 38.2 grams of biogas at a pressure of 100 Psi. Keywords: bamboo, biogas, ANG, Carbon Active, water mass flow rate